"Home Is Where My Couch Is": The Role of Possessions in the Process of Moving and Adjusting to Continuing Care Retirement Communities. (March 2019) - Green, Ohad; Ayalon, Liat
We examined the role of possessions in the process of moving and adjusting to continuing care retirement communities (CCRCs). Totally, 59 CCRC residents in 12 CCRCs were interviewed. We categorized three main types of residents: "I want it all, " "I want it that way, " and "I want to break free." Each type experienced differently the role that objects play in (a) the reasons for moving, (b) choosing a CCRC and a specific apartment, (c) organizing one's belongings in preparation for relocation, and (d) adjusting to the new apartment. Most residents were attached to their belongings and reported having great difficulty leaving them behind. Our findings suggest that while older adults should be given every possible opportunity to make their own choices about their belongings, it is also necessary to balance between the desire to maintain continuity with their past, and the limited space of a CCRC apartment.